Traumatic Separation of Bipartite Patella Underlying Gout - Eun Seok Choi; Jae Ang Sim; Jae Yun Go; Young Gon Na (Journal of Trauma and Injury)
Gouty arthritis is a common crystal arthropathy, but gout tophus in the bipartite patella is a rare condition. This report presented a traumatic separation of bipartite patellar fragment caused by mild trauma in a patient with comorbid gout. When a patient with bipartite patella and underlying gouty arthritis complains of pain after trauma, clinical suspicion is needed about fragment separation of the bipartite patella.